Developing successful agriculture [ an Australian case study - Zhou, Zhang-Yue (CABI, 2013)
This book showcases the development of Australian agriculture and draws implications for other countries about what they could learn from the lessons and experiences of Australian agriculture. It is written chiefly for agricultural and rural policy makes in government departments and international development agencies, leaders of peak bodies of agricultural industries, researchers, agribusiness consultants and university undergraduates and postgraduates who study courses related to agricultural and rural development. There are ten chapters in this book, organized into three parts. Part I highlights the success of Australian agriculture (Chapter 1), which was achieved in a unique agricultural environment (Chapter 2). Part II (Chapters 3-9) examines the key experiences, causes or factors that have helped Australia's success in agricultural development. Issues addressed in Part II include institutional arrangements for agricultural development, protection of farmers' interests, agricultural deregulation, farmer entrepreneurship, agricultural R&D, agricultural innovations and sustainable farming. The final part, Part III, consists of Chapter 10, which shows Australian initiatives in handling emerging challenges forfuture agricultural success.